Prostate-Specific Antigen Reduction After Androgen Receptor Pathway Inhibitor Initiation: Real-World Comparison of Disease Progression Among Patients With Metastatic Castration-Sensitive Prostate Cancer - Shawn Du; Carmine Rossi; Ibrahim Khilfeh; Porpong Boonmak; Gordon Wong; Dominic Pilon; Lorie Ellis (Journal of Health Economics and Outcomes Research)
# Background Prostate-specific antigen (PSA) has been used as both a screening tool and a marker for treatment response for advanced prostate cancer. With the introduction of androgen receptor pathway inhibitor (ARPI)-based treatment for metastatic castration-sensitive prostate cancer (mCSPC), there is a need to understand the impact that early treatment response, as measured by PSA, has on long-term clinical outcomes.